2013
DOI: 10.1074/jbc.m113.482000
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the GluN2A and GluN2B Subunits in Synaptic and Extrasynaptic N-methyl-d-aspartate Receptor Function and Neuronal Excitotoxicity

Abstract: Background:The function of NMDAR subtypes in neuronal signaling and excitotoxicity remains unclear. Results: GluN2A and GluN2B regulate both synaptic and extrasynaptic signaling and contribute to excitotoxicity. Conclusion: GluN2A and GluN2B play similar rather than opposing roles in NMDAR-mediated signaling and excitotoxicity. Significance: Knowing the function of NMDAR subtypes is critical for understanding how neuronal fate is regulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 58 publications
4
95
0
Order By: Relevance
“…Statistically significant differences from controls were determined by Student t test. * P \ 0.05 compared with control Our data also indicate that NMDA glutamate receptors participated in these effects since MK-801, a NMDA noncompetitive antagonist and ifenprodil, a blocker of extra-synaptic NR2B subunit-containing NMDARs (Zhou et al 2013a), totally prevented HMG-induced IF hypophosphorylation. Taking into account that activation of NR2B subunit results in inhibition of cAMP/PKA/ CREB signaling pathway (Corcoran et al 2013), it is proposed that HMG-elicited PKA down-regulation could be, at least partially, ascribed to the NR2B subunit.…”
Section: Discussionsupporting
confidence: 59%
“…Statistically significant differences from controls were determined by Student t test. * P \ 0.05 compared with control Our data also indicate that NMDA glutamate receptors participated in these effects since MK-801, a NMDA noncompetitive antagonist and ifenprodil, a blocker of extra-synaptic NR2B subunit-containing NMDARs (Zhou et al 2013a), totally prevented HMG-induced IF hypophosphorylation. Taking into account that activation of NR2B subunit results in inhibition of cAMP/PKA/ CREB signaling pathway (Corcoran et al 2013), it is proposed that HMG-elicited PKA down-regulation could be, at least partially, ascribed to the NR2B subunit.…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, ifenprodil was more effective than NVP-AAM077, a preferential GluN2A inhibitor, in reducing OGD-induced excitotoxicity as well as NMDAR-mediated elevation of [Ca 2+ ]i in cultured cortical neurons (Zhou et al, 2013a). In addition, the NMDA-induced cell death in hippocampal slices and cultured cerebrocortical neurons was found to be mediated by NMDAR containing GluN2B subunits, and insensitive to antagonists of GluN2A subunits Zhou and Baudry, 2006).…”
Section: Role Of Nmda Receptors In Excitotoxic Injurymentioning
confidence: 88%
“…Thus, the synaptic population of NMDAR was shown to mediate the excitotoxic damage in cultured hippocampal neurons subjected to hypoxic conditions and no protection was observed when extrasynaptic NMDAR were blocked (Wroge et al, 2012). A different set of studies, performed in cultured cortical neurons, showed no preferential coupling of synaptic or extrasynaptic NMDAR to excitotoxic injury (Zhou et al, 2013a). In the latter culture system, activation of synaptic or extrasynaptic NMDAR alone did not cause measurable cell death, but instead stimulated pro-survival signaling mechanisms (CREB, ERK, Akt).…”
Section: Activation Of Synaptic Vs Extrasynaptic Nmdar and Neuronal Dmentioning
confidence: 98%
“…IDO activity has been found in human fetal mixed brain cells but without differentiating which cell types express IDO and produce QA [48]. The presence of QA and enzymes involved in the production or metabolism of QA has been demonstrated in normal or pathological brain areas and it was accepted as an endogenous excitotoxin involved in NMDA receptor over activation-associated excitotoxicity [49][50][51]. In addition to production of excitotoxicity through activation of NMDA receptors, previous studies have shown that QA leads to neuroinflammation, and is involved in a variety of neurodegenerative diseases [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%